MOMEN INVARIANT UNTUK MENDAPATKAN CIRI DAUN TANAMAN HIAS - Abdul Kadir (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2010)
This paper describes a result of experiment in using moment invariant to obtain features of plants’s leaves that are invariant with scaling, rotation, and translation. This research was a preliminary in getting features that could be used to identify leaves of foliage plants. The focus was to analyse the application of invariant moment to various of leaves. The processing was done by using binary images, but its input was coloured image.